HALAL ATTITUDE AND VISIT INTENTION IN HALAL TOURISM IN INDONESIA - Listiawati, Listiawati; Usman, Bahtiar; Pratomo, Luki Adiati (Yayasan Education and Social Center, 2025)
Despite Indonesia securing the top rank in the 2024 Global Muslim Travel Index (GMTI), the national halal tourism sector continues to face substantial challenges, including low halal certification penetration, limited prayer infrastructure, and information asymmetry. This study aims to analyze the influence of halal awareness, halal certification, and halal knowledge on visit intention, with halal attitude as a mediating variable. Adopting a quantitative approach through hypothesis testing, data were collected from 290 respondents across 11 provinces in Indonesia, representing a heterogeneous religious background (37.2% Muslim and 62.8% Non-Muslim). Data analysis was conducted to map causal relationships among variables and identify factors contributing to the intention-behavior gap in the tourism context. The results indicate that halal certification and halal knowledge have a positive and significant impact on halal attitude. However, halal awareness was found to have no significant effect, a result likely attributed to the diverse religious backgrounds of the respondents, which influenced cognitive perceptions of halal attributes. A crucial finding of this study reveals that halal attitude fails to mediate the relationship between the independent variables and visit intention. This phenomenon confirms the existence of an